Evidências do efeito da fragmentação da mata atlântica na variabilidade e estruturação genética de Chiroxiphia caudata - Niero, Leonardo Paes (2014)
Habitat fragmentation is one of the main threats to biodiversity and one of the main challenges faced by conservation biology. This study assessed the habitat fragmentation effects on the genetic variability of Chiroxiphia caudata, which is an Atlantic Forest endemic bird species. Nine microsatellite loci were used for the analysis of individuals from five Atlantic Forest areas. We found departure from HWE is due to heterozygotes deficit and positive values for the inbreeding coefficient (Fis) for all populations. Private alleles were found in all areas. Fst, Dest, Bayesian and factorial correspondence analyses indicated that populations are genetically structured, but the distance could not explain the differentiation between areas. Apparently, this species did not suffered from a reduction in its variability because of the habitat fragmentation process. The fragmentation and its consequences as the reduction of gene flow may be acting in order to increase the differentiation between areas, including nearby areas that already show evidence of early differentiation.The choice of C. caudata for this study concerning the Atlantic Forest revealed the most fragmented areas played an important role for the specie by sheltering great genetic diversity within itself. Although not considered a very specialized specie as to their habits, the study model based on C. caudata showed that even more generalist species may be affected by fragmentation. When dealing with more specialized species, this scenario can become even worse.